Single‐photon emission from a further confined InGaN/GaN quantum disc via reverse‐reaction growth. Issue 3 (24th June 2019) - Sun, Xiaoxiao; Wang, Ping; Sheng, Bowen; Wang, Tao; Chen, Zhaoying; Gao, Kang; Li, Mo; Zhang, Jian; Ge, Weikun; Arakawa, Yasuhiko; Shen, Bo; Holmes, Mark; et al.
Abstract: We demonstrate high‐purity single‐photon emission from a high‐quality and further confined InGaN (indium gallium nitride) quantum disc in a GaN (gallium nitride) nanowire fabricated by an unconventional and versatile reverse‐reaction fabrication method. This further confined structure exhibits single‐photon emission with a g (2) (0) value of 0.11 at 8 K with a sub‐nanosecond radiative lifetime. The formation of the further confined structure using this versatile reverse‐reaction fabrication approach overcomes many limitations in conventional self‐assembled III‐nitride nanowires and, thus, exhibits a strong potential application as a high‐purity single‐photon source.